(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Studies on the recovery of lithium and cobalt from spent lithium-ion batteries have attracted much in recent years. For a sustainable battery industry, processes for the recycling of valuable metals from spent batteries via a "green" approach have been constantly being improved and developed. In this work, an effective process for the recycling of lithium and cobalt from used lithium batteries of mobile phones using HCl solution at low concentrations combined with H. sabdariffa flower extract was studied. The effect of parameters like concentration of the extract and HCl, pulp density, reaction temperature, and time on the leaching percentage of metals was investigated. In these leaching systems, the extract containing organic compounds acts as complexing and reductive agents for dissolved metals. Optimum conditions for the leaching of these metals were 90% (v/v) of the extract, 0.5 mol/L HCl, 10 g/L pulp density, 90oC, and 2.0 hours and 100% Li(I) and 91.3% Co(II) were leached under the optimum leaching conditions. Li(I) and Co(II) from leachate were fully separated by using AG®50W-X4 resins and the presence of the extract in the leaching solution trivially affected the recovery capacity of these metals. The metal loading capacity of the resin was determined to be 37.4 mg/g Co(II) and 1.2 mg/g Li(I). Thus, the use of plant extracts like H. sabdariffa flower can be considered a promising agent for the recovery of valuable metals from spent batteries.